PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BINGO REVIEW DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIISMPN 33 PADANG - Marianto, Marianto; Anggraini, Villia; Mardiyah, Ainil (STKIP PGRI Sumbar, 2014)
ABSTRACTComprehension of mathematical concept of students in class VIII of SMPN 33 that still low. This is why students do not like learning mathematical. One way that is used to overcome this problems is type of active learning strategies Bingo Review. This research was aimed at revealing whether the use type of active learning strategies Bingo Review could give a better effect on the students comprehension of mathematical concept than the conventional learning in class VIII of SMPN 33 Padang. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in students comprehension of mathematical concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and homogeny variant. Hypothesis test results obtained tcount = 2.47 and ttable = 1.664, indicating that the hypothesis was accepted. So, it was concluded that the application of Bingo Review strategies could improve the students comprehension of mathematical concept better than the conventional learning